INSPECTION FIL OF NURSING PERIOPERATIVE - Luciana Grittem; Maria Helena Rodrigues da Silva; Vera Lucia Scremin Miranda (Universidade Federal do Paraná, 2000)
The purpose of this work is to report the experience of creating and implementing nurses´s visits to patients during pre-operative period with the intention to provide continuous care during intra and post-operative periods. For such, a form was created, called Nursing Visit Form. After tests in three units, the form was implemented, being agreed that it would be attributed to the nurses in the admition units. The results show that there is the need for bigger commitment by the nurses in relation to the visits, as well as greater scientific knowledge regarding surgical procedures. Further studies on the impact of the nurse´s visit on the quality of assistance provided after surgical act are required.